IMPLEMENTATION OF PSC COST RECOVERY AND PSC GROSS SPLIT CONTRACTS IN THE IYP FIELD - Irvan Yulian Pratama; Satiyawira, Bayu; Yulia, Prayang Sunny (Petro : Jurnal Ilmiah Teknik Perminyakan, 2024)
In producing oil and gas, Indonesia has two valid contract schemes, namely PSC Cost Recovery and PSC Gross Split. The IYP field is a field that has great potential in producing petroleum, with 25 workover and 2 infill wells. The scheme released to compare with the PSC Cost Recovery scheme is the Gross Split PSC scheme. The previous scheme was considered to be ineffective and still detrimental to the government. So the government issued Ministerial Regulation No. 52 of 2017 which is the result of a revision of Permen no. 8 of 2017. Gross Split PSC Scheme, the contractor bears all operational costs for the development of oil and gas fields. The economic research on the IYP field aims to compare the Cost Recovery PSC scheme with the Gross Split PSC.